Investment and employment opportunities in China - Forrest, Jeffrey Yi-Lin, 1959-; Lixin, Tao (Systems evaluation, prediction, and decision-making series., 2015)
Presenting the most recent statistical data, Investment and Employment Opportunities in China provides first-of-its-kind coverage of the regional economic, industrial, investment, and employment structures in China. After establishing the theoretical foundation, the rest of the book utilizes the model and the methodology presented by the authors to analyze the various investment and employment structures within China. Addressing the problem of strategic optimization of macroeconomic systems, the book illustrates the current state of investment and employment opportunities in more than 30 provin.